2019
DOI: 10.1136/bmjopen-2018-028210
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with maternity waiting home use among women in Jimma Zone, Ethiopia: a multilevel cross-sectional analysis

Abstract: ObjectiveTo identify individual-, household- and community-level factors associated with maternity waiting home (MWH) use in Ethiopia.DesignCross-sectional analysis of baseline household survey data from an ongoing cluster-randomised controlled trial using multilevel analyses.SettingTwenty-four rural primary care facility catchment areas in Jimma Zone, Ethiopia.Participants3784 women who had a pregnancy outcome (live birth, stillbirth, spontaneous/induced abortion) 12 months prior to September 2016.Outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 36 publications
7
54
3
Order By: Relevance
“…Our study identified low utilization of MWHs was linked with socio-economic, demographic, cultural, and facilityrelated constraints. Only 42.5% of women in our study utilized MWHs, which is higher than previous studies done in Ethiopia, 24,25 and Zambia (27.3%). 26 The availability of MWHs in all health centers in the study area, the recent health policy of the government of Ethiopia targeting to decrease the maternal and child mortality, the presence of health extension workers (HEWs) who can reach out to the grass-root level community and linking their service to the next level health institutions in Ethiopia are possible explanations accounting for the use of MWHs being higher than those reported in the previous studies mentioned above.…”
Section: Discussioncontrasting
confidence: 75%
“…Our study identified low utilization of MWHs was linked with socio-economic, demographic, cultural, and facilityrelated constraints. Only 42.5% of women in our study utilized MWHs, which is higher than previous studies done in Ethiopia, 24,25 and Zambia (27.3%). 26 The availability of MWHs in all health centers in the study area, the recent health policy of the government of Ethiopia targeting to decrease the maternal and child mortality, the presence of health extension workers (HEWs) who can reach out to the grass-root level community and linking their service to the next level health institutions in Ethiopia are possible explanations accounting for the use of MWHs being higher than those reported in the previous studies mentioned above.…”
Section: Discussioncontrasting
confidence: 75%
“…This research is part of the Safe Motherhood Project, a mixed-methods intervention trial testing the rollout and scale up of interventions to reduce preventable maternal and newborn morbidity and mortality [41][42][43]. The Safe Motherhood Project has rolled out two interventions (an information, education and communication intervention, and maternity waiting area (MWA) upgrades) and conducted multiple rounds of data collection (prior to the design of the interventions, at baseline and at end line) [44].…”
Section: Study Approach and Designmentioning
confidence: 99%
“…The calculated sample size using the above assumptions was 663. In addition, the sample size for the barriers to MWH use (women's occupation, household index, and travel time to obstetric care facility) [29] was computed yet the result yielded a smaller sample size than the level of utilization. An additional 10% from the estimated sample size was considered to compensate for potential non-responses and multiplying the design effect by two, and the nal sample size for the study was 814.…”
Section: Sample Size Determination and Sampling Techniquementioning
confidence: 99%